2007
DOI: 10.1016/j.ijheatmasstransfer.2006.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Measuring temperature of the ice surface during its formation by using infrared instrumentation

Abstract: A non-destructive remote sensing technique was used to measure the surface temperature of a thin macroscopic water film flowing on a growing asymmetric ice accretion during its formation inside an icing research wind tunnel. Given the underlying thermodynamic conditions of this experimental series, the recorded surface temperature was always below the temperature of water fusion, T m =273.15 K, even when water shedding from growing ice accretions was observed visually. The surface temperature of ice accretions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Karev et al () measured the spatial distribution of the surface temperature of a non‐rotating icing cylindrical rod simulating a riming hailstone in the laboratory using a remote infrared camera and experimentally confirmed the model predictions of Lozowski et al (). They showed that, even with a wet regime near the stagnation line, the outer regions of the cylindrical hailstone remained in dry growth.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Karev et al () measured the spatial distribution of the surface temperature of a non‐rotating icing cylindrical rod simulating a riming hailstone in the laboratory using a remote infrared camera and experimentally confirmed the model predictions of Lozowski et al (). They showed that, even with a wet regime near the stagnation line, the outer regions of the cylindrical hailstone remained in dry growth.…”
Section: Resultsmentioning
confidence: 60%
“…When ice crystals impact on such a surface they have an increased chance of rebounding off the captured layer of ice crystals on the hail surface. Furthermore, it is interesting to note that, during wet growth, Karev et al () observed that the dry poles of the hailstone showed the presence of white rime feathers. It has been suggested that a possible charge separation mechanism when ice crystals interact with a graupel particle is the break‐up of tiny ice structures on the surface (Avila and Caranti, ).…”
Section: Resultsmentioning
confidence: 99%
“…Thermal images were corrected for emissivity, air temperature, and relative humidity. We assumed a uniform local emissivity of 0.96 based on emissivity values of water for smooth ice [Karev et al, 2007;Lingen et al, 2003]. Relative temperatures were systematically computed at different elevations (Z) at 8 cm intervals, using the spotmeter tool in the software ThermaCAM Research Professional 2.10 ( Figure 1d).…”
Section: Methodsmentioning
confidence: 99%
“…At this period, the surface is under a runback icing condition, which means a water-ice mixed state, and the temperature of such condition is set at 273.15 K (the freezing point) in the thermodynamic model during simulation. The possible reasons for the temperature difference between experiment and simulation are as follows: (1) The supercooled water film runback phenomenon, which is observed in the experiments [26][27][28], has not been considered in the present model. In simulation, the temperature of the runback water film would not be lower than the freezing point temperature (273.15 K).…”
Section: International Journal Of Aerospace Engineeringmentioning
confidence: 99%